Continuous Professional Development (CPD) Model Development for Vocational Lecturers - Antoni Arif Priadi; Retno Sawitri Wulandari; Suhartini Suhartini (Politeknik Ilmu Pelayaran Semarang, 2023)
Lecturers are professional educators and scientists with the main tasks of transforming, and disseminating science, technology and art through education, research and community service. Education in this century is a big challenge. The dominance of knowledge in education and learning must be able to be wise in using machines for benefit. To create quality lecturers, lecturer professional development is needed to improve their abilities. This study aims to develop a comprehensive and structured Continuous Professional Development (CPD) model to achieve standardized educational goals for vocational lecturers in the nautical study program at the Sekolah Tinggi Ilmu Pelayaran (STIP). Qualitative research with a population of 37 lecturers and a sample of 24 lecturers. The sample technique was purposive sampling. Data analysis techniques using descriptive statistics. The results showed that the value of a continuous professional competency development model required 47% of lecturers' perceptions, 47% of required perceptions of heads of research and community service departments, 61% of needed perceptions of heads of study programs, 61% of needed perceptions of leadership elements (chairman/deputy chairperson) 59%, the perception of the head of the quality assurance unit/headquarters is urgently needed 66% and the perception of the head of the lecturer group is needed 77% apprenticeship on ships.